Jonah and the whale : Bible story sound book - Parade, North (United Kingdom : North Parade, 2013)
PICTURE STORYBOOKS. Follow the story of forgiveness in Jonah and the Whale. Discover how and why Jonah is rescued from a terrible storm at sea by a giant whale. This book is a simple and dramatic retelling for young children of the favourite Old Testament story.
Keywords: Bible Stories -- Children's literature -- Forgiveness